Practical Astigmatism : Planning and Analysis. - Alpins, Noel (SLACK, Incorporated, 2017)
The surgical correction of astigmatism is the last frontier to optimizing visual outcomes for patients. Practical Astigmatism: Planning and Analysis is a comprehensive guide to correcting astigmatism from pre-operative planning to post-operative analysis. This provides readers with unique insight to what actually happened surgically: did the astigmatism over or under correct? Was it on-axis or off-axis? With this book, ophthalmologists will be able to analyze previous procedures with the appropriate nomograms and more often achieve targeted outcomes.